The first reported case of plasma cell granuloma of the larynx from Nepal - Nabin Lageju; Prakash Khanal; Shuvash Acharya; Samriddhi Karki; Nimesh Lageju; Durga Neupane (Otolaryngology Case Reports, 2022)
Plasma cell granuloma is a non-neoplasticclonal proliferation of plasma cells. It commonly involves the lungs. However, it may involve other organs as well but the involvement of the larynx is extremely rare. As the involvement of the larynx looks like a malignant mass, proper diagnosis and treatment are important. The treatment is surgical excision. However other treatment modalities can be oral steroids and radiation therapy. Here, we represent a case of plasma cell granuloma involving the larynx in an adult.